The surrealist toy, or the adventures of the bilboquet. (2019) - Hopkins, David
Abstract : The role of the toy, as a source for visual surrealism, has hardly been considered before now and even within avant-garde studies the toy is only just beginning to be looked at as an exemplar for modernist/avant-garde art. A growing literature on play has begun to register the importance of the ludic in Dadaist practice. Yet the surrealist toy has remained under-examined. Toys as (predominantly) three-dimensional objects lend themselves particularly well to sculpture. This essay therefore brings the specificities of the toy, surrealism and sculpture together in a new alignment through study of the bilboquet, an eroticized toy popular in France during the early twentieth century. This toy was the subject of a bawdy joke between Marcel Duchamp and a friend and might have been Duchamp's first readymade.